Ideologiska strategier och maskulin rationalitet: Kirunas stadsomvandling - Nilsson, Bo (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
Kiruna is a relatively young and small town in the north of Sweden. Due to the expansion of the mining industry parts of the central Kiruna has to move a few kilometers in a northwest direction. About ten percent of the population are in the long run going to be affected by the relovation. The mining company, LKAB, and Kiruna municipality argue for the necessity of the city moving, and the same view is reproduced by local and nationwide media. This article discusses the ideological strategies involved in the argumentation for a relovation, e.g. the use of historical perspectives and the production of a king of utopian future. The article also discusses how a semitraditional masculinity is reproduced through this argumentation and its focus on technological aspects of for example moving houses and building new roads. Social, cultural and emotional aspects are more or less invisible in the process.